Shape-specific preparatory activity mediates attention to targets in human visual cortex. - Stokes, M; Thompson, R; Nobre, A; Duncan, J (2009)
The mechanisms of attention prioritize sensory input for efficient perceptual processing. Influential theories suggest that attentional biases are mediated via preparatory activation of task-relevant perceptual representations in visual cortex, but the neural evidence for a preparatory coding model of attention remains incomplete. In this experiment, we tested core assumptions underlying a preparatory coding model for attentional bias. Exploiting multivoxel pattern analysis of functional neuroimaging data obtained during a non-spatial attention task, we examined the locus, time-course, and functional significance of shape-specific preparatory attention in the human brain. Following an attentional cue, yet before the onset of a visual target, we observed selective activation of target-specific neural subpopulations within shape-processing visual cortex (lateral occipital complex). Target-specific modulation of baseline activity was sustained throughout the duration of the attention trial and the degree of target specificity that characterized preparatory activation patterns correlated with perceptual performance. We conclude that top-down attention selectively activates target-specific neural codes, providing a competitive bias favoring task-relevant representations over competing representations distributed within the same subregion of visual cortex.